2020
DOI: 10.1093/mnras/staa039
|View full text |Cite
|
Sign up to set email alerts
|

The High Time Resolution Universe Pulsar Survey – XVI. Discovery and timing of 40 pulsars from the southern Galactic plane

Abstract: We present the results of processing an additional 44 % of the High Time Resolution Universe South Low Latitude (HTRU-S LowLat) pulsar survey, the most sensitive blind pulsar survey of the southern Galactic plane to date. Our partially-coherent segmented acceleration search pipeline is designed to enable the discovery of pulsars in short, highly-accelerated orbits, while our 72-min integration lengths will allow us to discover pulsars at the lower end of the pulsar luminosity distribution. We report the discov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This is also shown in Figure 2. However, we note that these DM-distance estimates typically come with large uncertainties 13 , making a definitive determination difficult. Additionally, the McMillan Galactic potential model 10 we have used in our analysis has known shortcomings at distances of approximately 7-9 kpc in the central regions of the Galaxy near PSR J1757-1854's position, further complicating this assessment.…”
Section: Proper Motion and The Radiative Test Of Gravitymentioning
confidence: 92%
“…This is also shown in Figure 2. However, we note that these DM-distance estimates typically come with large uncertainties 13 , making a definitive determination difficult. Additionally, the McMillan Galactic potential model 10 we have used in our analysis has known shortcomings at distances of approximately 7-9 kpc in the central regions of the Galaxy near PSR J1757-1854's position, further complicating this assessment.…”
Section: Proper Motion and The Radiative Test Of Gravitymentioning
confidence: 92%
“…After folding, an optimized S/N of 14.3 was obtained, well above the false alarm threshold, S/N thresh = 9 of our search. The non-detection of PSR J1325−6253 in previous processing of the survey conducted by Ng et al (2015) and Cameron et al (2020) was due to the segmented nature of their pipeline. In those searches, the 72-min full-length observations were only searched for accelerations, |𝑎| ≤ 1 m s −2 and higher acceleration searches were only performed on segmented observations where the sensitivity of a pulsar signal is degraded by a factor of √ 𝑁, where 𝑁 in the number of segments of the full integration observation.…”
Section: Discovery Of Psr J1325−6253 In Htru-s Lowlatmentioning
confidence: 99%
“…Their orbits therefore closely resemble that of the immediate post-SN state and can be used to constrain the mass-loss and kicks NSs receive at birth in such systems. In this paper we present the discovery and timing analysis of the binary pulsar PSR J1325−6253 which was discovered in a reprocessing of the High Time Resolution Universe South Low Latitude (HTRU-S LowLat) pulsar survey (Keith et al 2010;Ng et al 2015;Cameron et al 2020). PSR J1325−6253 is the second DNS system discovered in the survey after PSR J1757−1854, which remains the most accelerated known pulsar in a Galactic DNS system (Cameron et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We searched for single pulses up to the DM of 3000 pc-cm −3 with pulse widths ranging from 0.3 to 77 ms. We were able to constrain the presence of isolated 1 ms wide single pulses with a 6σ sensitivity of 25 mJy. Additionally, a 72-min integration at 1.5 GHz was re-processed from the High Time Resolution Universe South Low Latitude (HTRU-S LowLat) pulsar survey (Cameron et al 2020) in a line of sight near C1709−3918, but no pulsations were found (Vishnu Balakrishnan and Rahul Sengar, private communication).…”
Section: Pulsation Searchesmentioning
confidence: 99%